Módulo de Software para la Vinculación Laboral de Actores de la Carrera de Ingeniería en Sistemas/Computación - Merino Valverde, Diego Stalin (2022)
Currently, the employment relationship is an important factor for graduates of university careers, where the lack of socialization of job offers is the reason why job referrals cannot be generated. Based on this, the objective of this Degree Project (TT) is to implement a software module for the job placement of actors in the Systems/Computer Engineering Career, to answer the following research question: How to promote the process of job placement for students and graduates of the Systems/Computer Engineering Career through ICTs? The present TT consisted of three phases. In the first phase, the labor linkage process was defined using the BPM: RAD methodology, with the participation of the career management and the person in charge of graduate follow-up, together with the UNL's SISEG regulations. In the second phase, the development and design of the software module were carried out, using the requirements specification based on the IEEE 830 standard, the XP methodology with the Laravel Lumen and Angular tools, and the client-server architecture. Finally, in the third phase, an implementation plan was developed with its respective execution in a real environment, where a feasibility study, task scheduling, risk identification, functional analysis, and the development of support material such as user manuals and video tutorials were carried out. In this way, it was concluded that the implementation of an employment exchange contributes to generating labor referrals in an automated way and at the same time maintain a database that favors the follow-up of graduates, thus, aiming to know and access job offers by the actors of the Systems/Computer Engineering career. Keywords: Classified ads, XP methodology, lumen, angular, employment relationship, National University of Loja, software development.